Special report: Competing on knowledge - Bessant, John; Birkinshaw, Julian; Delbridge, Rick; Griffith, Rachel l.; Haskel, Jonathan; Neely, Andrew (Blackwell Publishing Ltd, 2008)
Traditionally, the UK has been regarded as good at innovation - with many inventions and scientific breakthroughs. So, can this nation rest easy? No. Based on extensive research by the Advanced Institute of Management Research (AIM), it would appear that the agenda for keeping Britain competitive is a demanding one. Six AIM authors report on what the UK needs to know. And do.